2011
DOI: 10.2478/v10237-011-0062-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of Injury among Professional Soccer Players

Abstract: O bjectives: Numerous empirical studies suggest that specific psychological factors influence the frequency and severity of sport injuries. The main purpose of the present study is to outline the psychological factors, which predict increased injury vulnerability among professional male soccer players in Denmark. Based on the Stress-Injury Model by Williams & Anderson (1998) it is hypothesized that low coping resources, high competitive trait anxiety, and history of previous injuries would be positively rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
0
27
0
2
Order By: Relevance
“…Of these injuries, 52 were traumatic and 12 were non-traumatic. For the present study, because we were interested in determining whether perfectionism predicted injury, we treated injury as a dichotomous variable (i.e., injured: 1 = yes, 0 = no; e.g., Hegedus et al, 2016; see also Devantier, 2011). 1…”
Section: Methodsmentioning
confidence: 99%
“…Of these injuries, 52 were traumatic and 12 were non-traumatic. For the present study, because we were interested in determining whether perfectionism predicted injury, we treated injury as a dichotomous variable (i.e., injured: 1 = yes, 0 = no; e.g., Hegedus et al, 2016; see also Devantier, 2011). 1…”
Section: Methodsmentioning
confidence: 99%
“…En los últimos años, a pesar de la prolífica producción científica (para una revisión véase Olmedilla, Ortega, Abenza y Boladeras, 2011), la inmensa mayoría de investigaciones centran sus objetivos en analizar las consecuencias psicológicas de la lesión deportiva y el comportamiento del lesionado en el camino a su plena recuperación, siendo escasos los estudios que analicen la relación entre factores psicológicos y la producción de lesiones. Además, entre éstos últimos, la gran mayoría de los mismos toman como muestra de estudio a deportistas de disciplinas de equipo (Abenza et al, 2009;Devantier, 2011;Ivarsson y Johnson, 2010;Johnson, 2011;Johnson, Eken- Los objetivos de este estudio son los siguientes: 1) conocer la incidencia de lesiones en deportistas de tecnificación deportiva de cuatro modalidades olímpicas individuales, y sus posibles diferencias en cuanto a sexo, disciplina practicada, categoría de competición y nivel competitivo, y 2) analizar la asociación entre personalidad, ansiedad rasgo competitiva y características psicológicas ligadas al rendimiento deportivo, con las lesiones deportivas.…”
Section: Introductionunclassified
“…However, Ivarsson et al studied a Swedish cohort and found that trait anxiety, negative life event and daily hassles were significant predictors for injury (Ivarsson et al, 2013). In addition, Devantier studied Danish players and found that player ability to cope with adversity was a main predictor for injury occurrence (Devantier, 2011).…”
Section: Psychological Factorsmentioning
confidence: 99%